2007
DOI: 10.1111/j.1439-037x.2007.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Antioxidative Enzymes, Sulphur Assimilation, Photosynthetic Activity and Growth of Wheat (Triticum aestivum) Cultivars Differing in Yield Potential Under Cadmium Stress

Abstract: The increasing concentration of cadmium (Cd) in agricultural soil has resulted in crop productivity loss. The activation of the antioxidative enzyme system and its synergy with sulphur assimilation may be required as one of the mechanisms for the alleviation of the effects of Cd. In the present study the activities of antioxidative enzymes and sulphur assimilation were studied in Cd‐treated wheat (Triticum aestivum) cultivars to assess their involvement in determining yield potential. The cultivar WH542 (low y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
94
2
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(113 citation statements)
references
References 60 publications
(97 reference statements)
11
94
2
6
Order By: Relevance
“…As observed in the present study, the growth inhibition may be consequence of Cd interference with the vital metabolic processes such as photosynthesis and translocation of photosynthetic products and essential nutrients. 4,10,[22][23][24] Cd stress significantly reduced the photosynthetic characteristics, such as P N , gs, CA activity and Chl content. The extent of reduction in photosynthetic characteristics was found to be higher in RH30 among all cultivars.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…As observed in the present study, the growth inhibition may be consequence of Cd interference with the vital metabolic processes such as photosynthesis and translocation of photosynthetic products and essential nutrients. 4,10,[22][23][24] Cd stress significantly reduced the photosynthetic characteristics, such as P N , gs, CA activity and Chl content. The extent of reduction in photosynthetic characteristics was found to be higher in RH30 among all cultivars.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have also reported reduction in photosynthesis under Cd stress. 4,19,22,25 Siedlecka et al reported that Cd affects photosynthesis by inhibiting different reaction steps of Calvin-cycle. Significant reduction in net photosynthetic rate, stomatal conductance, Rubisco activity, CA activity and chlorophyll content was noted in the presence of Cd.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cadmium exposure significantly affected essential ions in roots and shoots has been explored in rice (Liu et al, 2003), wheat , barley (Wu and Zhang, 2002) and lettuce (Monteiro et al, 2009). These mineral nutrients also have specific of defensive role against lethal effects of Cd (Khan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%